Broadscale phage therapy is unlikely to select for widespread evolution of bacterial resistance to virus infection. Issue 2 (25th August 2020) - Cohan, Frederick M; Zandi, Matthew; Turner, Paul E
Abstract: Multi-drug resistant bacterial pathogens are alarmingly on the rise, signaling that the golden age of antibiotics may be over. Phage therapy is a classic approach that often employs strictly lytic bacteriophages (bacteria-specific viruses that kill cells) to combat infections. Recent success in using phages in patient treatment stimulates greater interest in phage therapy among Western physicians. But there is concern that widespread use of phage therapy would eventually lead to global spread of phage-resistant bacteria and widespread failure of the approach. Here, we argue that various mechanisms of horizontal genetic transfer (HGT) have largely contributed to broad acquisition of antibiotic resistance in bacterial populations and species, whereas similar evolution of broad resistance to therapeutic phages is unlikely. The tendency for phages to infect only particular bacterial genotypes limits their broad use in therapy, in turn reducing the likelihood that bacteria could acquire beneficial resistance genes from distant relatives via HGT. We additionally consider whether HGT of clustered regularly interspaced short palindromic repeats (CRISPR) immunity would thwart generalized use of phages in therapy, and argue that phage-specific CRISPR spacer regions from one taxon are unlikely to provide adaptive value if horizontally-transferred to other taxa. For these reasons, we conclude that broadscale phage therapy efforts are unlikely to produce widespread selection for evolution of bacterial resistance.